2021
DOI: 10.3389/frvir.2021.647896
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Embodiment Short Questionnaire

Abstract: Consumer virtual reality (VR) technologies have made embodying a virtual avatar during an immersive experience more feasible. The sense of embodiment toward that virtual avatar can be characterized and measured along three factors: self-location, agency, and body ownership. Some measures of embodiment have been previously proposed, but most have not been validated or do not measure the three individual factors of embodiment. In this paper, we present the construction and validation of a preliminary version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The first challenge comes from measurement development. Only three paper deals with scale development (Eubanks et al, 2021; Kim, 2013; Peck & Gonzalez‐Franco, 2021). However, there is still a lack of measurement instruments that take into account the structural complexity of virtual embodied experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first challenge comes from measurement development. Only three paper deals with scale development (Eubanks et al, 2021; Kim, 2013; Peck & Gonzalez‐Franco, 2021). However, there is still a lack of measurement instruments that take into account the structural complexity of virtual embodied experience.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, considering virtual embodied experience is a multi‐dimensional construct, existing measurements might be insufficient to capture its comprehensive content. So it is necessary to develop virtual embodied experience measurement ahead of existing measurement solutions, which mainly focus on bodily experience (e.g., Eubanks et al, 2021; Peck & Gonzalez‐Franco, 2021) while rarely touching other experiential orientations. Considering that there are many subliminal or under‐conscious components in such an experience, conventional paper‐and‐pencil scales should be extended to include more measuring operations, such as ZMET (Jung et al, 2019), video analysis (Reinhard et al, 2020), eye‐tracking (Luis del Campo et al, 2018), EEG (Müller et al, 2017), fMRI (Seinfeld et al, 2021), and SCRs (Rosa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The experience will not be the same when using controllers to teleport their avatar or using full-body tracking to move themselves. Eubanks et al (2021) found that having foot tracking significantly improves the SoA and the SoSL compared to head-and-hands tracking or no tracking at all. Moreover, Waltemate et al (2016) observed that motor performance is affected by latency (induced by signal transmission and processing of tracking) when it is above 75 ms, and it also impacted negatively the SoA when the latency is higher than 125 ms.…”
Section: The Sense Of Agencymentioning
confidence: 91%
“…Once the 15 repetitions had been performed, the experimental condition finished and the participant gave the experimenter the controller and the head mounted display. Then, the participant answered the preliminary Embodiment Short Questionnaire (pESQ) to evaluate the sense of embodiment during that experimental condition, with the selected combination of real and virtual hands, focusing on three factors: self-location, agency and body ownership [ 38 ]. Besides, a short questionnaire based on previous studies [ 39 ] was included to evaluate if participants had had any positive (fun, relaxing, challenging, distracting or others) or adverse (dizziness, fatigue, anxiety or others) reactions during the experimental condition.…”
Section: Methodsmentioning
confidence: 99%